Effect of PHP Preprocessing and Optimization of Enzymatic Saccharification on Bioethanol Production from Teki Grass with Its Benefits as Ship Fuel in Supporting Energy Availability for Ship Fuel in Coastal Areas - Rosyidah Khoirunnisa Al-ghiffary; Riyad Khoirul Anam (Maritime in Community Service and Empowerment, 2024)
The availability of environmentally friendly energy as ship fuel in coastal areas is one of the challenges faced today. One alternative that can be used is bioethanol. This study analyzed the potential of Cyperus rotundus (teki grass) as the main ingredient of bioethanol G2 through preprocess-PHP and optimization of enzymatic saccharification. Preprocess was carried out at two temperatures (40°C and 50°C) with time variations, followed by saccharification and fermentation using Aspergillus niger and Saccharomyces cerevisiae. The results showed that optimal saccharification in preprocessing at 50° C produced 13.66% cellulose content. The best bioethanol content was obtained at a fermentation time of 7 days with a temperature of 38°C. This research contributes to the development of an effective method for producing bioethanol from teki grass, supporting the sustainability of renewable energy while considering environmental aspects.